The effect of urea resins synthesized with different mole ratios on physical properties of high density fiberboards (HDF) and formaldehyde emission - Osman Çamlıbel (Turkish Journal of Forestry, 2021)
The indispensable product of living spaces, the raw material of high density fiberboard (HDF) based derivative products (laminate flooring derivatives, etc.) are HDF boards. The test values (physical and formaldehyde emission properties ) of HDF boards are targeted both physical properties and formaldehyde emission E1 or E0 standard. In this study, 50% yellow pine (Pinus sylvestres L), 30% fir (Abies nordmanniana L), 20% beech (Fagus orientalis L) were used biomass. HDF boards of 7.7mmx2100mmx2440mm were produced on the production line which using three different moles of urea-formaldehyde resins (R; 1.17, X; 0.98 and Y; 0.88). Production parameters remained constant in the HDF line process and the only variable were urea formaldehyde resins used in three different molar ratios. The productions were manufactured in pressing speed of 950 mm/second and pressing temperature 215ºC and 60 seconds pressing time in the continue hot press. R, X, Y HDF boards produced; physical tests (thickness, density, board moisture, 24 hours Thickness-swelling and 24 hours water absorption) and formaldehyde gas emissions were analysed which was five boards were measured from each test group. Physical properties of HDF boards were measured which was the density of boards (R; 874 kg/m³, X; 881 kg/m³ and Y; 860 kg/m³) Thickness swelling of boards at 24 hours (R; 17.79%, X; 19.65% and Y; 19.08%) water absorption of boards at 24 hours (R; 19.65%, X; 19.09% and Y; 22.42%). Formaldehyde gas emission result of HDF boards were analysed (R; 14.96, mg/100g. X; 8.28 mg/100g and Y; 6.79 mg/100g). As a result of the study, differences were determined according to both physical test results and formaldehyde gas emission results for HDF boards produced.